A Morphological Analysis Of Affixes Used In Tempo Magazine January 2013 Edition - Azmi, Yuwaida; , Dra. Dwi Haryanti, M.Hum; , Siti Fatimah, S.Pd, M.Hum (2013)
This research paper aims at answering the objectives of this research are: (1) to identify the kinds of affixes used in Tempo Magazine January 2013 edition and (2) to describe the forms and meaning of each. The type of the research is descriptive qualitative research and this research uses documentation and observation methods to get the data. Then, the technique of analyzing data are identifying the words which include affixes, analyzing the words that are containing affixes, and drawing conclusion based on data analysis. The data are words consisting affixes taken from the articles on the magazine. The writer concern with three articles which are entitled: "New routes for the postman", "Living with Risk", "Indonesia Partnership Landscape" as object of the study. The research finding of the study shows that the types affixes and the data of this research consists of 310 English affixes include prefix "in-"which changes the meaning. Prefix "re-" which changes noun into verb, prefix "un-" which changes adjective into adverb, prefix "dis-" which changes noun into verb, prefix "pre-" which indicates present tense, prefix "anti-" which changes verb into noun. And suffix "-s" which indicates present tense, suffix "-ed" which changes noun into verb, suffix "-ly" which changes adjective into adverb, suffix "-er" changes verb into noun, suffix "-ment" which changes verb into noun, suffix "-ness" changes adjective into noun, suffix "-ity" which changes adjective into noun, suffix "-ist" which indicates plural noun, suffix "-ive" which changes verb into adjective, suffix "-ize" which changes noun into verb, suffix "-able" which changes verb into adjective, suffix "-ion" which indicates singular noun, suffix "- ism" which indicates singular noun, suffix "-ship" which indicates singular noun, suffix "-y" which changes verb into noun, suffix "-en" which indicates past tense, suffix "-ing" which changes verb into noun, suffix "-est" which indicates superlative, and suffix "-ful" which indicates verb into adjective. In conclusion, the meaning of affixes that used in the data source is indicator of changing the class of the category. At the end of analysis, the researcher finds that the addition of affixes into the word would influence either the meaning of the existing word.